Plasma cell rich acute rejection: Risk factors, treatment and outcomes - Satish Mendonca; Ananth Rao; Manu Dogra; Vivek Sood; S Prakash; G Batta; A Dua; A Joshi; U K Sharma; R Tiwari (Saudi Journal of Kidney Diseases and Transplantation, 2021)
Plasma cell-rich rejection is a rare and poorly defined entity. Its treatment is not clearly defined and has universally poor prognosis. More data should be published from various transplant centers around the world to identify the treatment that has the best outcomes and to formulate treatment guidelines for these cases. It is a retrospective analysis of kidney biopsies form 2008 to 2018. Four hundred biopsied were screened and 55 were found to have features of rejection and among them, 13 had plasma cell-rich rejection. Data of treatment given and the graft survival outcomes in these cases were retrieved by medical records. One patient had complete recovery, three had graft loss and the remaining nine had permanent decline in glomerular filtration rate. Decrease in immunosuppression and presence of infection are risk factors for plasma cell-rich acute rejection (PCAR). It can be acute cell-mediated rejection (ACR)/antibody-mediated rejection (AMR)/ACR+AMR. Resistant rejection, ACR+AMR, C4d positivity, and severe interstitial inflammation are poor prognostic factors. Overzealous decrease in immunosuppression should not be done. Management of immunosuppression during infection is most critical for the development of PCAR. Bortezomib is emerging as a therapeutic modality for the treatment of PCAR.